What is the role for treatment of hyperlipidemia in the primary prevention patient? - Richard M Fleming; Matthew R Fleming; Tapan K Chaudhuri (Journal of Cardiovascular Medicine and Cardiology - Peertechz Publications, 2020)
It is reported that Hippocrates said If someone wishes for good health, one must first ask oneself if he is ready to do away with the reasons for his illness. Only then is it possible to help him and Our food should be our medicine and our medicine should be our food.